2020
DOI: 10.1038/s41559-020-01322-x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of biological impacts of artificial light at night

Abstract: A meta-analysis of 126 published studies shows that exposure to artificial light at night induced strong responses for physiological measures, daily activity patterns and lifehistory traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
250
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 270 publications
(252 citation statements)
references
References 150 publications
0
250
2
Order By: Relevance
“…ALAN exposure is known to harm a vast array of species on Earth [27]. Organisms at or near the surface of the Earth experience natural illumination levels spanning nine orders of magnitude with the timing and duration of those exposures largely determined by the Sun and Moon.…”
Section: Ecologymentioning
confidence: 99%
“…ALAN exposure is known to harm a vast array of species on Earth [27]. Organisms at or near the surface of the Earth experience natural illumination levels spanning nine orders of magnitude with the timing and duration of those exposures largely determined by the Sun and Moon.…”
Section: Ecologymentioning
confidence: 99%
“…Artificial light at night (ALAN) is a globally widespread environmental pollutant with direct ecological impacts on multiple terrestrial and aquatic ecosystems [1][2][3] including ecosystem functioning [4]. ALAN has been identified as a new major pollutant in the context of global environmental change [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent meta-analysis, addressing a wide variety of impacts, found no evidence for a systematic increase in effect sizes with levels of ALAN (Sanders et al 2021). Moreover, it has been shown that the complexities of cascading effects through food webs can mean that lower intensities have greater impacts than higher ones .…”
Section: Light Levelsmentioning
confidence: 97%